Pendidikan Kesehatan Skrining Neonatal Pada Bayi Baru Lahir Untuk Masyarakat Desa Betung Barat, PALI - Sari, Bunga Anggreini; Septiani, Tety; Muslimin, Muslimin; Kurnianingsih, Susi; Juniarti, Ariska (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The infant mortality rate (IMR) serves as a crucial indicator in assessing public health. Congenital abnormalities are one of the leading causes of infant mortality in Indonesia. Neonatal screening aims to detect congenital abnormalities early to improve infants’ quality of life. This community service activity aimed to enhance the knowledge of the residents of Betung Barat Village, Penukal Abab Lematang Ilir, regarding the importance of neonatal screening. The event took place on February 20, 2025, using lectures and discussion methods, attended by 30 participants. Evaluation through pre-test and post-test questionnaires showed a significant increase in knowledge, with the average score rising from 55.3 to 78.7 (p = 0.005). These results indicate that education is effective in improving community understanding of neonatal screening. It is recommended to conduct regular educational programs, involve families in supporting neonatal screening, and enhance access to information through local media and village health volunteers to improve infant health from an early stage.